PENGEMBANGAN KARIR DAN KOMPENSASI MEMPENGARUHI KEPUASAN KERJA KARYAWAN PADA PT. PRIMA TETAP LESTARI JAKARTA SELATAN - Ferdian; Nariah (Journal of Research and Publication Innovation, 2024)
This research aims to determine the effect of career development on employee job satisfaction at PT. Prima Fixed Lestari, this research uses quantitative methods. The sampling technique uses a saturated sample and a population of 60 employees. The data collection technique in this research used a questionnaire. The analysis method uses instrument testing, classical assumption testing, regression testing, correlation coefficient and determination coefficient testing and hypothesis testing. The research results show that career development (X1) influences job satisfaction (Y) by obtaining the regression equation Y= 6.748 + 0.744 X1. Hypothesis testing shows a calculated t value of 13.503>2,001 or a sig probability of 0.000<0.5. Meanwhile, the correlation value is 0.871, which means it has a very strong influence. The determination value is 75.9% while the remaining 24.1% is influenced by other factors. Compensation (X2) influences job satisfaction (Y) by obtaining the regression equation Y = 5.239 + 0.796 X2. Hypothesis testing shows a calculated t value of 15.586>2,001 or a sig probability of 0.000<0.5. Meanwhile, the correlation value is 0.898, which means it has a very strong influence. The determination value is 80.7% while the remaining 19.3% is influenced by other factors. And career development (X1) and compensation (X2) have a positive and significant effect on job satisfaction (Y) by obtaining the regression equation Y=4.097 + 0.319 X1 + 0.510 X2. Meanwhile, the correlation value is 0.918, which means it has a very strong influence. The determination value is 84.3% while the remaining 15.7% is influenced by other factors. Hypothesis testing obtained Fcount > Ftable (152.601 > 2,001), this was also strengthened by the probability significance of 0.000 < 0.05.